The effectiveness of immersive simulations in studying nutrient chemical transformations in higher education institutions - Fedash, Maiia (Академічні візії, 2026)
The relevance of this study is driven by rising expectations for the quality of specialist training in the natural sciences and biomedical disciplines amid the digital transformation of higher education, as well as by the complexity of disciplinary content that requires the integration of molecular, metabolic, physiological, and technological mechanisms. The multilevel nature of nutrient chemical transformations imposes a substantial cognitive load and necessitates the use of innovative pedagogical tools capable of supporting a coherent, system-level understanding of biochemical processes. The aim of the article is to provide a theoretical rationale for implementing immersive simulations in the teaching of nutrient chemical transformations in higher education institutions and to determine their educational potential for improving the quality of learners’ professional preparation. To achieve this aim, the study employs analytical synthesis of the scholarly literature, systematization of approaches to educational process digitalization, structural and logical analysis of the cognitive complexity inherent in biochemical disciplines, and comparative analysis of the functional capacities of immersive technologies in professional education. The findings indicate a high integrative and cognitive level of complexity in nutrient chemical transformations and confirm the effectiveness of immersive simulations as a tool for interactive modeling of biochemical processes. Their potential to foster systems thinking and to develop learners’ analytical and predictive competencies is substantiated. The study also identifies key scientific and practical challenges associated with implementing immersive technologies, including the lack of standardized integration models, limited empirical verification of long-term educational effects, and technical and organizational constraints. The conclusions emphasize the appropriateness of systematic integration of immersive simulations into educational programs in the natural sciences and biomedical disciplines. Future research directions include developing valid instruments for evaluating the effectiveness of immersive learning, empirically testing its long-term impact on learners’ professional preparation, and establishing an evidence-based model for the digital transformation of biochemical education.